Pusztulás, gyász, remény. Bibliai teológiai szempontok a közösséget ért veszteség feldolgozásához - HODOSSY-TAKÁCS, Előd (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
Doom, Grief, Hope. Perspectives of Biblical Theology for Processing Community Loss. Crisis is an unavoidable part of community and individual life, and traumas can have long-lasting effects on societies. Community loss index is a relatively recent indicator, before introducing it to the sphere of theology, in the present paper, two questions are addressed: (1) is the state of loss indeed necessary?; (2) how is it possible to cope with such a loss or collapse on a theologically acceptable way? We evaluate certain historical events from the perspective of community loss and gain (King Hezekiah of Judah and the Assyrian crisis, the Babylonian exile), with special focus on prophetic pronouncements, sermons (Ezekiel, Jeremiah) and eschatology. The author makes a sharp difference between historical events and their literary representations. As a final word, the necessity of grief as a prerequisite of a successful future is emphasised.